Reproductive Toxicity Test of Plants-Derived Insecticide in Male Rats - Kanokporn Saenphet (Science Faculty of Chiang Mai University, 2019)
This study evaluated the safety of bioinsecticide derived from Stemona curtisii Hook. F. and Mammea siamensis Kosterm. on reproductive system of male rat. The rats were orally administered with bioinsecticide at the doses of 2, 10 and 50 mg/kg body weight for 60 consecutive days in comparison with 2 mg/kg body weight of methomyl. It was found that rats treated with the bioinsecticide and methomyl showed a significant decrease in testis, seminal vesicle and prostate weights when compared to control rats (p < 0.05). Nevertheless, a decrease in epididymal sperm concentration and the histopathological alterations of the rat’s testes were found only in rats treated with methomyl, but not with bioinsecticide.